AMYGDALA RESPONSE TO NEGATIVE STIMULI PREDICTS PTSD SYMPTOM ONSET FOLLOWING A TERRORIST ATTACK. Issue 10 (3rd July 2014) - McLaughlin, Katie A.; Busso, Daniel S.; Duys, Andrea; Green, Jennifer Greif; Alves, Sonia; Way, Marcus; Sheridan, Margaret A.
<x xml:space="preserve">Abstract</x> Objective Individuals with posttraumatic stress disorder (PTSD) exhibit heightened amygdala reactivity and atypical activation patterns in the medial prefrontal cortex (mPFC) in response to negative emotional information. It is unknown whether these aspects of neural function are risk factors for PTSD or consequences of either trauma exposure or onset of the disorder. We had a unique opportunity to investigate this issue following the terrorist attacks at the 2013 Boston Marathon and the ensuing manhunt and shelter in place order. We examined associations of neural function measured prior to the attack with PTSD symptom onset related to these events. Methods A sample of 15 adolescents (mean age = 16.5 years) who previously participated in a neuroimaging study completed a survey assessing posttraumatic symptoms related to the terrorist attack. We examined blood oxygen level dependent (BOLD) response to viewing and actively down‐regulating emotional responses to negative stimuli in regions previously associated with PTSD, including the amygdala, hippocampus, and mPFC, as prospective predictors of posttraumatic symptom onset. Results Increased BOLD signal to negative emotional stimuli in the left amygdala was strongly associated with posttraumatic symptoms following the attack. Reduced bilateral hippocampal activation during effortful attempts to down‐regulate emotional responses to negative stimuli was also associated with greater posttraumatic symptoms. Associations of amygdala reactivity with posttraumatic symptoms were robust to controls for pre‐existing depression, anxiety, and PTSD symptoms and prior exposure to violence. Conclusions Amygdala reactivity to negative emotional information might represent a neurobiological marker of vulnerability to traumatic stress and, potentially, a risk factor for PTSD.